PELAKSANAAN PASAL 155 KOMPILASI HUKUM ISLAM TENTANG KETENTUAN IDDAH BAGI JANDA PUTUS PERKAWINAN KARENA KHULU’ DI KANTOR URUSAN AGAMA KECAMATAN SIMO KABUPATEN BOYOLALI - Zahroh, Siti; Syamsuddin, Syamsuddin; Baehaqi, Baehaqi (IBLAM LAW REVIEW, 2023)
This research is a qualitative research with a descriptive narrative literature approach that takes literature as its source and interviews. The data collection technique in this study is considering that this research uses library research. To analyze the data the writer will do a qualitative analysis. This form of analysis is carried out with explanations, not in the form of statistical figures or other figures. The method used in analyzing this data uses the deductive method, namely "a study in which people depart from general knowledge, with the starting point of that general knowledge, we want to assess a specific incident. The results of this study are the implementation of the iddah period in article 155 KHI at the Regional Office of Religious Affairs in Simo District, Boyolali Regency, starting with the issuance of the decision of the Religious Court and the length of the iddah from 3 sacred times to 7 sacred times and Iddah provisions for widows who break up due to khulu' in article 155 KHI in the Maqasid sharia perspective according to Article 155 of the Compilation of Islamic Law (KHI) is the iddah period for widows who break up because khulu', fasakh and li'an apply iddah talak. From the above article it can be understood that there is clearly no difference between the iddah of a woman imposed by the khulu' and the iddah of a woman who was divorced by her husband, namely three times quru' or three times purification. KHI equates iddah khulu' with iddah divorce. From this term, khulu' is equated with divorce as well as the legal consequences that arise, including in this case regarding reducing the number of divorces and in terms of iddah provisions.